2021
DOI: 10.1016/j.whi.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Self-Perceived Fecundity among Young Adult U.S. Women

Abstract: Background: Individuals' perceptions of their fecundity, or biological ability to bear children, have important implications for health behaviors, including infertility help-seeking and contraceptive use. Little research has examined these perceptions among U.S. women. Methods: This cross-sectional study examines perceptions of one's own fecundity among U.S. women aged 24 to 32 who participated in the 2009-2011 rounds of the National Longitudinal Survey of Youth (1997) cohort. Analyses were limited to 3,088 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…This belief also reaches beyond Africa. Studies in the United States [ 14 , 15 ], Guatemala [ 16 ], Turkey [ 9 ], Bangladesh [ 17 , 18 ], and Vietnam [ 19 ] reported that this fear is a barrier to contraception use. A systematic review of barriers to contraception use among young people in low to middle income countries reported that the belief that contraception use would cause infertility was the most cited reason for non-use [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This belief also reaches beyond Africa. Studies in the United States [ 14 , 15 ], Guatemala [ 16 ], Turkey [ 9 ], Bangladesh [ 17 , 18 ], and Vietnam [ 19 ] reported that this fear is a barrier to contraception use. A systematic review of barriers to contraception use among young people in low to middle income countries reported that the belief that contraception use would cause infertility was the most cited reason for non-use [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, among women who said that there was no chance or they were unlikely to become pregnant, under half (43%) also reported experiencing infertility. Therefore, it is possible that women are making determinations about their future fertility based on factors that may not be reliable (Gemmill, Sedlander, and Bornstein 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly little research has paid specific attention to describe and understand low perceived susceptibility to pregnancy (notable exceptions come from Frohwirth, Moore, and Maniaci 2013, Polis and Zabin 2012, and Gemmill, Sedlander, and Bornstein 2020. These beliefs are a common barrier to contraceptive use and have meaningful sociodemographic variation.…”
Section: Discussionmentioning
confidence: 99%